Are we yet sick of new technologies?: the unequal health effects of digitalization - Arntz, Melanie; Findeisen, Sebastian; Maurer, Stephan; Schlenker, Oliver (Working Paper Series, 2024)
This study quantifies the relationship between workplace digitalization, i.e., the increasing use of frontier technologies, and workers' health outcomes using novel and representative German linked employer-employee data. Based on changes in individual-level use of technologies between 2011 and 2019, we find that digitalization induces similar shifts into more complex and service-oriented tasks across all workers, but exacerbates health inequality between cognitive and manual workers. Unlike more mature, computer-based technologies, frontier technologies of the recent technology wave substantially lower manual workers' subjective health and increase sick leave, while leaving cognitive workers unaffected. We provide evidence that the effects are mitigated in firms that provide training and assistance in the adjustment process for workers.
Keywords: Graue Literatur